ANALISA PERHITUNGAN ENERGI LISTRIK PADA SEPEDA LISTRIK HYBRID - Dhimas Satria; Rina Lusiani; Haryadi Haryadi; Imron Rosyadi (University of Muhammadiyah Jakarta, 2017)
In this increasingly modern era, many needs are increasing, one of which is energy. Fossil energy has long been the main fuel used on machines. Excessive use of energy further decreases the availability of fossil energy. To reduce the dependence on fossil energy that its formation is very long and quickly exhausted, hence the need for the utilization of alternative energy more environmentally friendly and easy to get. In this research, electrical energy analysis on hybrid electric bikes is done. In this analysis includes the utilization of electrical energy and electrical energy consumption on a hybrid electric bike with the test results to utilize the energy wasted on a hybrid electric bike at a speed of 25 km / h when the horizontal road condition is 9.36 watts. Whereas with the utilization of wasted energy at a speed of 20 km / h when the road conditions horizontally, the generator generated power of 8.16 watts. While on road conditions decreases at a speed of 15 km / h when the road conditions decrease is 3 watts and at a speed of 10 km / h power raised by 0.03 watts. For electric energy consumption of power used by hybrid electric bikes at the initial loading with a distance of 25 meters and travel time of 12.83 seconds is 87.61 watts, while for horizontal road conditions at a constant speed of 20 km / h is 29.42 watts with Covering 475 meters. While the power used by a hybrid electric bike on a ride load up to 25 meters with a slope of 220 at a speed of 5 km / h will consume power of 483.85 watts.